Developing An Adventure Game For Teaching Arabic To Develop Critical Thinking Skills Of Elementary School Students/ تطوير اللعبة المغامرات حبا لتعليم اللغة العربيةفي تنمية مهارة التفكير الناقذ لدى طلاب المرحلة الإبتدائية - Qomariyah, Lailatul; Bahrodin, Ariga (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Educational games are a form of learning media that educates and where media can stimulate students to improve their critical and creative thinking skills and carry out joint activities between students in learning activities. Adventure Game is an exciting game to develop because it has the advantage of visualizing real problems in Arabic learning. This article aims to develop Hubba’s adventure game to improve critical thinking skills for elementary-level students. This study used Five steps. That is, analysis, design, development, implementation, and evaluation. It was shown that the educational game Hubba’s Adventure can improve students' thinking by 32.79%, so it can be said that the game is effectively applied to learn the subject